Sexual Behavior and its Relationship with Semen Quality Parameters in Jaffrabadi Breeding Bulls - Chaudhart, JK; solanki, JB; Vijeyta, HP; Gamit, PM; Murthy, KS (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
The present study was carried out on 80 ejaculates, 20 each from four healthy Jaffrabadi breeding bulls to see the relationship between sexual behavior and semen quality parameters. The results depicted that the overall mean values of libido score, mating ability score and sexual behavior score of four bulls were 45.83 ± 1.04, 78.79 ± 0.82 and 63.81± 0.77, respectively, with significant (p <0.05) difference in libido score between bulls. The overall color of semen ranged from thin white to very thick creamy. The overall values for semen volume (ml), pH, sperm concentration (million/mL), mass activity, individual sperm motility (%) and live spermatozoa (%) were 2.99 ± 0.12, 6.80 ± 0.01, 1439.68 ± 48.46, 3.94 ± 0.03, 89.51 ± 0.21 and 95.00 ± 0.19, respectively. The values for semen volume, sperm concentration, mass activity (%) and live sperm (%) differed significantly (p <0.05) between bulls. There were significant positive correlations (p <0.01) of libido with mating ability, sexual behavior score and ejaculate volume of semen (r = 0.37 to 0.87), while a negative correlation was found with sperm concentration (-0.30). Mating ability was significantly (p <0.01) correlated with sexual behavior score and ejaculate volume (0.78, 0.67), and sexual behavior was correlated with semen volume (0.84). Sperm concentration was significantly (p <0.05) correlated with mass activity (0.29), while individual sperm motility was positively (p <0.05) correlated with live sperm percentage (0.25). Correlations of libido, mating ability and sexual behavior with other semen quality parameters were negligible and negative. The study reflected the importance of sexual behavior of Jaffrabadi bulls in predicting their future utility as a proficient breeder under AI program.